Graphetic variation within one scribal hand as evidence on manuscript production - Varila Mari-Liisa (Routledge Taylor & Francis Group, 2022)
This paper explores the potential benefits of analysing graphetic variation for philological and textual research on manuscript material. For this pilot study, two gatherings from two mid-sixteenth-century English manuscripts were analysed. The gatherings share some of their texts and are written by the same scribe. According to a set of five criteria defined in this paper, variation in word-final s forms was selected as an example of graphetic variation. The distribution of two variant forms of word-final s was studied in order to locate possible changes in preference. The results show that analysing the distribution of graphetic variants may reveal discontinuities in textual production, for example where one scribal stint ends and another begins. Together with codicological and textual evidence, an analysis of graphetic variation can be helpful in determining the textual structure of manuscripts and establishing the chronological sequence of manuscript production. The method can also be used for the purposes of palaeography, especially scribal identification. The approach could be further tested in order to determine which graphemes and other visual features are suitable for such an analysis and to form a diagnostic set of those features.